Elementary School Curriculum Management In Improving Disaster Preparedness In Areas With Potential Disasters In Ngepanrejo Public Elementary School - Supriyatno, Arie; Tawil, Tawil; Imaniar, Holy Nikmah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Ngepanrejo Village, Bandongan Magelang Subdistrict has hilly morphology with a slope between 20 ° to 25 °. This condition has the potential for landslides. This situation results in disruption of the community, including learning activities at educational institutions in the area. This study aims to determine primary school curriculum management in improving disaster preparedness in disaster-potential areas at SD Negeri Ngepanrejo. A qualitative descriptive research design with the subject of the principal, teachers, and students totaling 30 personnel. Data collection techniques by interview, observation, documentation and questionnaires. Test the validity of the data using source triangulation. The data analysis used was the Miles and Huberman model, namely data reduction, data presentation, and data verification / conclusion drawing. The results of the study concluded that 1) curriculum planning, learning tools, assessment programs and structural organization were guided by KTSP, contained the Disaster Safe Education Unit (SPAB) program, and were organized. 2) The implementation of the curriculum goes well, 3) The curriculum evaluation uses the CIPP model and is able to have a positive impact on the generation of disaster preparedness.